Το θέμα της «σγουραφιστής στόρησης» των δύο πρωταγωνιστών στον Ερωτόκριτο: : Ερμηνευτικά ζητήματα λόγου και εικόνας - Ροδοσθένους-Μπαλάφα Μαρίνα (Σύγκριση/Comparaison/Comparison, 2023)
The “painted image” of the two protagonists in Erotokritos: Interpretive issues of language and image In this study, we aim to explore the relationship between literature and art theory by examining Vitsentzos Kornaros’s romance Erotokritos, focusing specifically on the two portraits created by the protagonists, Erotokritos and Arete, for each other. Our analysis will involve a comprehensive examination of the way these portraits were received and commented on by the protagonists and the poet in relation to the materials and techniques applied. To contextualize Kornaros’s poetic verses concerning the theme of painting, we will consider the philosophical backdrop of the time. This will entail a discussion of Marsilio Ficino’s Commentary on Plato’s Symposium on Love. Additionally, we will refer to significant treatises on art, such as Leon Battista Alberti’s renowned work On Painting (De Pictura, 1435-1436). We will enhance our understanding of the theme by drawing upon other important sources in the field. For example, we will reference Giorgio Vasari’s influential work The Lives of the Artists (1550, 1568) and Leonardo da Vinci’s notes on painting (1452-1519). Moreover, we will explore possible direct and indirect intertextual references to contemporary Greek and Italian literary works relating to portraiture. This will involve discussing the Cypriot Renaissance Collection of poems, Chortatsis’ Erofili, as well as sonnets by Bernardo Bellicioni, Giovane Della Casa, and Pietro Aretino. By engaging with these diverse sources and analysing the interactions between literature and art theory in Erotokritos, this study aims to contribute to a deeper understanding of the complex interplay between these two domains within the literary milieu of the time.